2012
DOI: 10.1161/circoutcomes.111.964460
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of Ranking Lists Based on Cardiac Surgery Mortality Rates

Abstract: Background-Ranking lists are a common way of reporting performance in cardiac surgery; however, rankings have shown to be imprecise, yet the extent of this imprecision is unknown. We aimed to determine the precision of, and fluctuations in, ranking lists in the comparison of cardiac surgery mortality rates. Methods and Results-Information on all adult cardiac surgery patients in all 16 cardiothoracic centers in The Netherlands from January 1, 2007, until December 31, 2009, was extracted from the database of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
0
15
0
2
Order By: Relevance
“…При анализе данных с помощью системы ES II оценивались факторы риска, связанные с характеристикой пациента, состоянием сердца и с операцией. Число факторов риска составило 6,9 [5,7], при гендерном анализе -у мужчин 6,3 [5,[3][4][5][6][7]1], у женщин 7,1 [6,[2][3][4][5][6][7]8] (р<0,05). Прогнозируемая госпитальная летальность -1,8 [1,5], в т. ч. у мужчин -1,3 [1,0-2,1], у женщин -3,3 [2,5-4,1] (р<0,05).…”
Section: результаты и обсуждениеunclassified
See 1 more Smart Citation
“…При анализе данных с помощью системы ES II оценивались факторы риска, связанные с характеристикой пациента, состоянием сердца и с операцией. Число факторов риска составило 6,9 [5,7], при гендерном анализе -у мужчин 6,3 [5,[3][4][5][6][7]1], у женщин 7,1 [6,[2][3][4][5][6][7]8] (р<0,05). Прогнозируемая госпитальная летальность -1,8 [1,5], в т. ч. у мужчин -1,3 [1,0-2,1], у женщин -3,3 [2,5-4,1] (р<0,05).…”
Section: результаты и обсуждениеunclassified
“…В современной кардиохирургии и анестезиологии отсутствуют общепризнанные методы оценки риска и предоперационной подготовки при КШ в зависимости от наличия сопутствующей и/или ассоциированной патологии с учетом гендерных различий. Так, несмотря на высокую оценку использования в кардиохирургии системы EuroSCORE (ES -European System for Cardiac Operative Risk Evaluation), в публикациях последнего времени накопились данные о недооценке или переоценке летальности на основе оценочной шкалы, в результате чего использование системы ES стало вопросом для дискуссий [7,8]. В обзорной статье, 2012г, обобщены результаты 67 исследований по определению прогностической точности показателя ES; сделан вывод, что оценка риска на основе этой модели не может применяться ни для отбора пациентов на кардиохирургическую операцию, ни для сравнения результатов между отдельными клиниками [9].…”
Section: Introductionunclassified
“…As a consequence, there is substantial fluctuation from one sampling period to another in the rates of adverse events and performance rankings among providers 32. Longitudinal assessment of provider performance over longer periods of time and investigation of trends are more prudent approaches than relying on results in one sampling period 33…”
Section: The Limitation Of Small Sample Sizementioning
confidence: 99%
“…The influence of the hospital unit or a system of national health outcome in cardiac surgery has been studied in this context [ 11 ] . Siregar et al [ 12 ] showed the limitations of showing lists of performance of hospitals and surgeons in the study population of patients undergoing cardiovascular surgery in the Netherlands. The study shows that in a three-year period, there was great variability in the results of hospitals with wide confidence intervals, thus questioning the validity of such comparisons.…”
Section: Introductionmentioning
confidence: 99%